2011
DOI: 10.1093/icb/icr035
|View full text |Cite
|
Sign up to set email alerts
|

Heterothermy in Afrotropical Mammals and Birds: A Review

Abstract: Recent years have seen a rapid increase in the number of Afrotropical endotherms known to avoid mismatches between energy supply and demand by using daily torpor and/or hibernation. Among mammals, heterothermy has been reported in 40 species in six orders, namely Macroscelidea, Afrosoricida, Rodentia, Eulipotyphla, Primates and Chiroptera. These species span a range in body mass of 7-770 g, with minimum heterothermic body temperatures ranging from 1-27°C and bout length varying from 1 h to 70 days. Daily torpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 91 publications
1
71
0
Order By: Relevance
“…Even though heterothermy is a physiological response which is usually associated with cold conditions that coincide with short photoperiod, decreased food availability and food quality, summer torpor is not an unusual behaviour in mammals (reviewed by McKechnie and Mzilikazi 2011). It has been suggested that summer torpor could be advantageous during uncharacteristically dry summers or at low food availability.…”
Section: Discussionmentioning
confidence: 99%
“…Even though heterothermy is a physiological response which is usually associated with cold conditions that coincide with short photoperiod, decreased food availability and food quality, summer torpor is not an unusual behaviour in mammals (reviewed by McKechnie and Mzilikazi 2011). It has been suggested that summer torpor could be advantageous during uncharacteristically dry summers or at low food availability.…”
Section: Discussionmentioning
confidence: 99%
“…Although, birds are known to regulate body temperature to a high degree and within very narrow margins, there is building evidence that substantial deviations from normothermia naturally occur (Guillemette et al, 2016). Indeed, hypothermic events such as torpor is evident in many families of afrotropical birds while there are numerous studies reporting cases of controlled hypothermia as a strategy to conserve energy in temperate and arctic environments as well (McKechnie and Mzilikazi, 2011; Lewden et al, 2014). While T b may be lowered as an energy-saving mechanism in many bird species, the result of the high-energy demands imposed by flight, with flapping flight often being described as the costliest locomotion mode among vertebrates (Butler and Woakes, 1990; Butler, 2016), is associated with the highest levels of known heat production among endotherms (Clarke and Rothery, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence suggests that many birds from a diverse group of unrelated families may not maintain constant body temperature set points as originally assumed, and may instead demonstrate heterothermic flexibility in response to increased energetic costs of thermoregulation (McKechnie and Lovegrove 2002, McKechnie and Mzilikazi 2011, Brigham et. al.…”
Section: Introductionmentioning
confidence: 99%